n = 1 ∑ ∞ Γ ( n + 1 ) Γ ( n − 2 1 ) ( ψ ( n − 2 1 ) − ψ ( n + 1 ) ) = − a π ln b
Find a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Plus don't you just love it ,at one side is this huge disappointing sum but the answer is sooo elegant,to me mathematics should be like that.
Problem Loading...
Note Loading...
Set Loading...
You would be grossly disappointed about this explanation if you hadn't seen the discussion "on the iterated properties of Beta Function".Since, Γ ( x ) Γ ( y ) Γ ( x + y ) Γ ( y + 1 ) n = 1 ∑ ∞ Γ ( x + y + n ) Γ ( x + n − 1 ) ( ψ ( x + n − 1 ) − ψ ( x + y + n ) ) = ψ ( x ) − ψ ( x + y ) .Then simply letting x = 1 / 2 , y = 1 / 2 we have,
Γ ( 1 / 2 ) Γ ( 1 / 2 ) Γ ( 1 ) Γ ( 3 / 2 ) n = 1 ∑ ∞ Γ ( n + 1 ) Γ ( n − 1 / 2 ) ( ψ ( n − 1 / 2 ) − ψ ( 1 + n ) ) = ψ ( 1 / 2 ) − ψ ( 1 ) Since ψ ( 1 / 2 ) = − 2 ln 2 − γ , Γ ( 1 / 2 ) = π a n d ψ ( 1 ) = − γ .Then multiplying both sides by Γ ( 3 / 2 ) π and simplifying we have
n = 1 ∑ ∞ Γ ( n + 1 ) Γ ( n − 1 / 2 ) ( ψ ( n − 1 / 2 ) − ψ ( 1 + n ) ) = − 4 π ln 2 .Hence a=4 and b=2 ,a+b=6 .Sorry for complexity.